HUBUNGAN ANTARA KONDISI TAJUK Eucalyptus pellita F. Muell DAN INFEKSI PENYAKIT BUSUK AKAR - Luciasih agustini; Ragil S.B Irianto (Pusat Penelitian dan Pengembangan Hutan, 2016)
ABSTRACT Functional disruption of cells and tissues within individual leaves due to pests and diseases infection subsequently causes in deterioration of crown, canopy contraction, and even tree death. Crown condition usually used as visual indicator for tree health assessment. Root-rot is considered as the most damaging disease for Eucalyptus pellita plantations. Methodology for the detection of rootrot at an early stage is required. In order to develop root rot detection method, this study investigates relationship between crown symptoms and root rot disease in E. pellita plantation. A visual assessment method to classify the crown condition of trees in plantations of E. pellita was developed. Repeatability, reproducibility and reliability of the developed method were examined by conducting repeated surveys. Applicability of the method to indicate root-rot incidence and severity at individual tree level was tested in seven plots. At the plot level, the crown-conditions were significantly correlated with the incidence and severity of root rot. At the tree level, the crown conditions were not significantly correlated with root-rot incidence and severity. Probability of these crown-indicators for estimating root-rot incidence and severity in individual tree is 61.4% and 41.6%, respectively. In order to prevent risks of massive productivity loss, root-rot site risk assessments Functional disruption of cells and tissues within individual leaves due to pests and diseases infection subsequently causes in deterioration of crown, canopy contraction, and even tree death. Crown condition usually used as visual indicator for tree health assessment. Root-rot is considered as the most damaging disease for Eucalyptus pellita plantations. Methodology for the detection of rootrot at an early stage is required. In order to develop root rot detection method, this study investigates relationship between crown symptoms and root rot disease in E. pellita plantation. A visual assessment method to classify the crown condition of trees in plantations of E. pellita was developed. Repeatability, reproducibility and reliability of the developed method were examined by conducting repeated surveys. Applicability of the method to indicate root-rot incidence and severity at individual tree level was tested in seven plots. At the plot level, the crown-conditions were significantly correlated with the incidence and severity of root rot. At the tree level, the crown conditions were not significantly correlated with root-rot incidence and severity. Probability of these crown-indicators for estimating root-rot incidence and severity in individual tree is 61.4% and 41.6%, respectively. In order to prevent risks of massive productivity loss, root-rot site risk assessments are suggested to be conducted before plantation expansion.Keywords: Crown condition incidence, root rot, severity ABSTRAK Gangguan fungsional pada sel-sel dan jaringan daun akibat serangan hama dan penyakit dapat menyebabkan perubahan pada tajuk, penyusutan kanopi dan bahkan dapat menyebabkan kematian pohon. Kondisi tajuk merupakan indikator visual untuk menilai kesehatan suatu pohon. Penyakit busuk akar merupakan salah satu penyakit yang mengancam produktivitas tegakan dan sampai saat ini belum dapat dikendalikan dengan E. pellita efektif. Metode pendeteksian penyakit busuk akar melalui pengamatan karakteritik kondisi tajuk menjadi penting untuk diketahui. Penelitian ini bertujuan mengembangkan metode penilaian kondisi tajuk guna mengetahui hubungan antara kondisi tajuk dengan keberadaan dan tingkat keparahan penyakit busuk akar pada tegakan E. pellita. E. pellita Penelitian diawali dengan mengklasifikasikan kondisi tajuk ke dalam 5 kelas. Metode klasifikasi ini diuji , dan . Penerapan metode penilaian kondisi tajuk dalam menduga repeatability reproducibility reliability keberadaan dan level keparahan penyakit busuk akar diuji pada 7 plot pengamatan. Hasil penelitian menunjukkan bahwa pada level plot, kondisi tajuk . secara signifikan berkorelasi dengan serangan penyakit busuk akar. E pellita Namun, pada level individu pohon masih sulit dideteksi. Peluang kondisi tajuk . dalam menduga E pellita keberadaan penyakit busuk akar sebesar 61,4% dan tingkat keparahan sebesar 41,6%. Penilaian potensi suatu kawasan terhadap serangan penyakit busuk akar perlu dilakukan sebelum pembukaan hutan tanaman industri agar kerugian besar akibat penyakit busuk akar dapat dihindari.Kata kunci: , keberadaan, kondisi tajuk, penyakit busuk akar, tingkat keparahan